Revitalisasi pada Koperasi Unit Desa Berstatus Tidak Aktif: Studi Kasus di Kabupaten Pati - Jatmiko Wahyudi; Aeda Ernawati; Siti Qorrotu Aini (Universitas Proklamasi 45 Yogyakarta, 2021)
Revitalization is one of the government programs to re-empower rural cooperative (KUD) in Indonesia. Revitalization for inactive KUD has the purpose to reactivate KUD although the outcome is highly dependent on the conditions of the KUD as well as the internal support of the KUD. This study was conducted in two inactive KUDs in Pati Regency, Central Java namely KUD Sedyo Rukun Juwana and KUD Sukolilo. The research uses a qualitative approach with a case study design. Interviews and focus group discussion (FGD) was performed to collect data. The study aims to describe the conditions and the implementation of a revitalization program in both KUD. The results showed that both KUDs do not play a role as cooperative anymore. One of the indicators is that both KUDs has not carried out annual member meetings (RAT) for more than three years. Revitalization of KUD Sedyo Rukun Juwana was conducted by reorganizing and strengthening institutions through RAT. Conversely, the activation of KUD Sukolilo is nearly possible due to the complexity of the problem within the KUD. Liquidation of KUD Sukolilo can be an option to make clear the status of KUD. However, from a legal perspective, KUD Sukolilo cannot be dissolved because they experienced an inability to pay bad credit from the government.